An Insight into Z-Drug Abuse and Dependence: An Examination of Reports to the European Medicines Agency Database of Suspected Adverse Drug Reactions - Schifano, Fabrizio; Chiappini, Stefania; Corkery, John M; Guirguis, Amira (The international journal of neuropsychopharmacology, 2019)
Abstract Background Although originally marketed as safe alternatives to the habit-forming benzodiazepines, growing numbers of zaleplon, zolpidem, and zopiclone (“Z-drugs”) clinical concerns relating to their potential of abuse, dependence, and withdrawal have been reported over time. We aimed here at assessing these issues analyzing datasets of adverse drug reactions provided by the European Medicines Agency through the EudraVigilance system. Methods Analyzing the adverse drug reactions databases of each Z-drug, descriptive analyses have been performed on cases and proportional reporting ratios (PRRs) computed. Results An overall number of 33 240 (e.g., 23 420 zolpidem; 9283 zopiclone; and 537 zaleplon) misuse-, abuse-, dependence-, and withdrawal-related adverse drug reactions, corresponding to some 6246 unique patients given Z-drugs, were here identified. Cases were studied and described, including demographic characteristics and clinical data such as concomitant drugs, doses, routes of administration, and outcomes of the reactions (being fatalities recorded). Considering PRR values and in comparison with zopiclone, zolpidem was more frequently involved in both misuse/abuse and withdrawal issues. Zolpidem and zopiclone presented with the same dependence risk, but zopiclone was most involved in overdose adverse drug reactions. Compared with zaleplon, zopiclone presented higher dependence and overdose-related issues but slightly lower misuse/abuse and withdrawal PRR values. Conclusion Current data may only represent a gross underestimate of the real prevalence of Z-drug misuse. Caution should be exercised when prescribing those molecules, especially for patients with psychiatric illnesses and/or history of drug abuse. We recommend the need to invest in proactive pharmacovigilance activities to better and promptly detect, understand, and prevent any possible misuse potential of prescribed medications.